Refugees in higher education : debate, discourse and practice - Stevenson, Jacqueline; Baker, Sally (Great debates in higher education., 2018)
This book examines the key debates relating to the rights, responsibilities, policies and practices of the higher education sector when dealing with students from refugee backgrounds. Exploring the political context of forced migration to countries of settlement, including the impact made by media rhetoric, "Refugees in Higher Education" identifies how such global issues frame and position the efforts of universities to open access to, and enable the participation of, refugee students. Focusing on the UK and Australia (representing a past colonising and a colonised country) and including a series of individual case studies, it asks challenging questions about the discourses around forced migration, and how these play out for students on a personal level.With unprecedented levels of forced migration, and the growing strength of anti-immigration arguments as more power is conceded to alt-right conservative governments, "Refugees in Higher Education" is both a timely and much-needed contribution to its field.